2016
DOI: 10.4238/gmr.15017392
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic diversity of super sweet corn inbred lines using SSR and SSAP markers

Abstract: ABSTRACT. In this study, we compared the efficiency of simple sequence repeat (SSR) and sequence specific amplified polymorphism (SSAP) markers for analyzing genetic diversity, genetic relationships, and population structure of 87 super sweet corn inbred lines from different origins. SSR markers showed higher average gene diversity and Shannon's information index than SSAP markers. To assess genetic relationships and characterize inbred lines using SSR and SSAP markers, genetic similarity (GS) matrices were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…The gene diversity computed for the 268 sweet corn inbreds is likely to be overestimated, as stated before, due to unusual high residual heterozygosity at some loci, and thus, conclusion regarding genetic diversity in the sweet corns of public sectors in Thailand must be interpreted with caution. However, the gene diversity found in our sweet corns (0.71) was comparable to that found in 12 inbreds (0.64) reported by Ferreira et al (2018) and in 87 inbreds reported by Ko et al (2016).…”
Section: Genetic Diversity In the Sweet Corn Inbredssupporting
confidence: 83%
See 1 more Smart Citation
“…The gene diversity computed for the 268 sweet corn inbreds is likely to be overestimated, as stated before, due to unusual high residual heterozygosity at some loci, and thus, conclusion regarding genetic diversity in the sweet corns of public sectors in Thailand must be interpreted with caution. However, the gene diversity found in our sweet corns (0.71) was comparable to that found in 12 inbreds (0.64) reported by Ferreira et al (2018) and in 87 inbreds reported by Ko et al (2016).…”
Section: Genetic Diversity In the Sweet Corn Inbredssupporting
confidence: 83%
“…A total of 224 alleles were detected with the number of alleles per locus (N A ) ranging from 5 (markers umc1123, umc1394 and umc1276) to 20 (marker bnlg1033) with an average of 11.2 (Table 1). The average number of alleles per locus in our sweet corns was much higher than that in sweet corn germplasms previously reported by Ko et al (2016) (1.96 alleles per locus from 50 SSRs in 87 diverse sweet corn inbreds conserved in a public institute of Korea), by Mehta et al (2017) ). Nonetheless, the high number of alleles and alleles per locus in our study indicates wide genetic variation among the sweet corn inbred lines in the public sectors in Thailand.…”
Section: Ssr Variationcontrasting
confidence: 63%
“…They identified inbreds for synthesis of pools and populations to develop novel inbreds and prospective heterotic combinations in various genetic backgrounds (sh2sh2 x sh2sh2, su1su1 x su1su1, su1su1/sh2sh2 x su1su1/sh2sh2, sh2sh2 x su1su1/sh2sh2 and su1su1 x su1su1/sh2sh2). For maize-breeding programs in Korea, Ko et al [13] compared the efficiency of simple sequence repeat (SSR) and sequence specific amplified polymorphism (SSAP) markers for analyzing genetic diversity, genetic relationships, and population structure of 87 supersweet corn inbred lines from different origins. Even though supersweet corn has a narrow genetic origin and is not widely used in Korea; they found enough variability for breeding supersweet for Korea.…”
Section: Genetic Basis Of Modern Sweet Cornmentioning
confidence: 99%
“…QTL/modifier genes in the starch biosynthesis pathway may influence kernel sweetness (Qi et al 2009, Whitt et al 2002 in the sh2sh2/su1su1 genetic background. Wide genetic In view of the growing importance of sweet corn and to accelerate the pace of progress of sweet corn cultivar development, it is therefore, important to develop promising sweet corn hybrids with high kernel sweetness and per se productivity (Ko et al 2016, Mehta et al 2017. Only few centres in selected countries possess organized sweet corn breeding programmes, and hybrids are predominantly in the genetic background of either sh2sh2 or su1su1.…”
Section: Resultsmentioning
confidence: 99%